2017
DOI: 10.1177/1042258717725520
|View full text |Cite
|
Sign up to set email alerts
|

Betting on the Coachable Entrepreneur: Signaling and Social Exchange in Entrepreneurial Pitches

Abstract: Given that stakeholders often commit more than capital to a startup, they commonly stress how important it is for entrepreneurs to be “coachable.” To date, however, coachability has received little attention in entrepreneurship research. We address this gap by first establishing the entrepreneurial coachability construct and validating a measurement scale. Then, drawing on social exchange and signaling theories, we develop and test a novel framework in which coachability influences a potential investor’s willi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 74 publications
6
104
0
Order By: Relevance
“…Funding decisions by investors are almost by definition made after some form of social interaction with the entrepreneurs or team of entrepreneurs took place. One particular setting that facilitates interaction between new venture teams and prospective investors is where entrepreneurs have the opportunity to convey their business idea in an entrepreneurial pitch (Ciuchta et al 2018;Pollack et al 2012). Most often, investment decisions are made by bankers (e.g., Mason and Stark 2004), business angels (e.g., Clark 2008), or venture capitalists (e.g., Chen et al 2009;Shepherd et al 2003;Zacharakis and Shepherd 2001).…”
Section: Decision-making In Entrepreneurial Contexts Involving Socialmentioning
confidence: 99%
See 3 more Smart Citations
“…Funding decisions by investors are almost by definition made after some form of social interaction with the entrepreneurs or team of entrepreneurs took place. One particular setting that facilitates interaction between new venture teams and prospective investors is where entrepreneurs have the opportunity to convey their business idea in an entrepreneurial pitch (Ciuchta et al 2018;Pollack et al 2012). Most often, investment decisions are made by bankers (e.g., Mason and Stark 2004), business angels (e.g., Clark 2008), or venture capitalists (e.g., Chen et al 2009;Shepherd et al 2003;Zacharakis and Shepherd 2001).…”
Section: Decision-making In Entrepreneurial Contexts Involving Socialmentioning
confidence: 99%
“…Concerning investors' decisions, research on entrepreneurial passion has suggested that the demonstrated passion of an entrepreneur in a pitch directly influences investor decision-making (Cardon et al 2009;Chen et al 2009;Pollack et al 2012). Hence, nonverbal behavioral cues such as using animated facial expressions, a lot of gestures, and talking with varied tone and pitch could send signals of passion to investors in an entrepreneurial pitch (Nagy et al 2012;Ciuchta et al 2018). In addition, research and practice of entrepreneurship would suggest that coachability is very important for investors and, for example, an open hand gesture, mimicry, and attention through eye contact could influence investors' judgment of entrepreneurs' degree of coachability (Ciuchta et al 2018).…”
Section: A Conceptual Framework On Decision-making Involving Social Imentioning
confidence: 99%
See 2 more Smart Citations
“…We are also interested in theoretically and empirically robust papers that expand coaching to new work contexts and populations (e.g., entrepreneurs; Ciuchta, Letwin, Stevenson, McMahon, & Huvaj, ).…”
Section: Objectives and Scope Of The Special Issuementioning
confidence: 99%